1986
DOI: 10.1007/bf00250517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aeration rate and influence of pCO2 in large-scale cultures of Catharanthus roseus cells

Abstract: Summary.Catharanthus roseus cells were grown at various aeration rates using normal or CO2-enriched air. Kinetic data showed a detrimental effect of the increase of the gassing rate on the growth characteristics due to CO2 stripping. When the CO2 partial pressure in the culture was maintained at a constant level of 20 mbar, better growth and enhanced conversion yields were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
1
16
1
Order By: Relevance
“…Under conditions of unlimited oxygen a high level of carbon source utilization can be achieved, while oxygen limitation markedly reduces the conversion rate (88). Similar results can be obtained under carbon dioxide enriched and limited-conditions (89,90). Above a critical level both oxygen and carbon dioxide suppress the growth.…”
Section: Gaseous Environmentsupporting
confidence: 84%
See 1 more Smart Citation
“…Under conditions of unlimited oxygen a high level of carbon source utilization can be achieved, while oxygen limitation markedly reduces the conversion rate (88). Similar results can be obtained under carbon dioxide enriched and limited-conditions (89,90). Above a critical level both oxygen and carbon dioxide suppress the growth.…”
Section: Gaseous Environmentsupporting
confidence: 84%
“…Each method has its advantages and disadvantages. A special problem connected with the air-lift reactor is the growth inhibiting effect of high aeration rates (90,98,99). An alternative approach to the mixing problem might be modification of the medium in such a way that aggregates remain smaller even while cells sustain their biosynthetic capacity (61).…”
Section: Large-scale Fermentationmentioning
confidence: 99%
“…In addition, no detrimental effect on the growth characteristics was observed upon increasing the gassing rate when the partial pressure of carbon dioxide in the culture was maintained at a constant level of 20 mbar using CO2-enriched air as the sparging gas [2]. We concluded that carbon dioxide exerts a growth promoting effect during the early period of growth and that the pCO2 needs to be considered as an operating parameter to ensure optimal growth in largescale cultures.…”
Section: Introductionmentioning
confidence: 87%
“…In such fermentors, cultured plant cells showed little sensitivity for shear stress [115]. Pareilleux & Vinas [117], Ducos & Pareilleux [118] and Hegarty et al [119] studied the effect of the aeration rate on culture growth. Too high and too low rates lead to a suboptimum in dissolved CO2 concentrations, which inhibited growth.…”
Section: Aerationmentioning
confidence: 99%